Efecto de la aplicacion de fungicidas y del manejo cultural en la produccion y la calidad de la semilla de frijol, Phaseolus vulgaris L. - Estrada, EI (International Center for Tropical Agriculture, 1989)
Research was conducted to evaluate the application of a fungicide mix in the various stages of crop development and the effect of different selection systems in the production and final quality of the seed produced. Two cv. (Calima and PVA 916), 4 selection systems (plants, pods, seeds, and P + V + S), and 4 application rates (0, 2, 3, and 5) of a mix of the fungicides Benomyl (0.55 g/l) plus Mancozeb (3 g/l) were evaluated. The expt. was carried out during 1988, in Darien-Calima (1420 m.a.s.l.), Cordillera Occidental (Valle del Cauca, Colombia). For each plot in the field, no. of plants discarded and harvested, total grain yield, and pure seed yield were evaluated. Manual seed selection and physiologic and sanitary quality tests of the seeds were carried out in the lab. Results obtained show that there was a differential response as a result of the different application rates, with an increase in total production, pure seed yield, and seed quality with a greater application rate, being the optimum critical point around 3 applications. The best selection systems were those including seed selection. When 2 or 3 fungicide applications or a combination are made with a seed selection system, a high pure seed yield is obtained, with excellent quality. Determining some variable costs allows for comparing the positive effects of the various applications on production, quality, and value of the treatment. (AS-CIAT)